A Sectoral Development Model for MSMEs: Strategies for Sustainable Regional Empowerment - Pinto Jaya; Mashadi Mashadi; Sandy Wibisono (Program Vokasi dan LPPM IBI Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in sustaining regional and local economies, yet they face persistent challenges such as limited access to finance, inadequate human capital, weak digital adoption, and fragmented market networks. These problems are particularly acute at the micro-regional scale, where infrastructure and institutional capacity are constrained. This study proposes a sectoral development model of MSMEs at regional and micro-regional levels as a strategy for sustainable economic empowerment. The model integrates four key elements: identification of local sectoral potentials, clustering of MSMEs based on sectoral strengths, integration of digital and green innovations, and multi-stakeholder collaboration. Data were drawn from literature review, secondary data, and a limited survey of 30 MSMEs in Java and Eastern Indonesia, complemented by a case study of the Jepara furniture cluster. Findings indicate that sectoral clustering enhances productivity, competitiveness, and resilience, while digital adoption and green practices contribute to long-term sustainability. The model has implications for policy design, financing schemes, and regional economic planning, and highlights the roles of government, academia, financial institutions, private actors, and communities. This research contributes a novel framework that bridges theory and practice, offering actionable insights for strengthening MSME resilience and aligning local economic development with the Sustainable Development Goals. Keywords: MSMEs, sectoral development, regional economy, micro-regional clusters, sustainable empowerment, digital transformation, green innovation